The impact of the spread of the Corona pandemic (COVID-19) on motivations (health, social and psychological) to practice sports activities in Syria - حسون حنان; انجيلا ماضي (Latakia University Journal -Medical Sciences Series, 2023)
In order to identify the changes imposed by the spread of the (COVID-19) pandemic on society, the impact of the spread of the pandemic on the health, social and psychological motives in Syrian society was studied. Accordingly, a questionnaire was designed and distributed electronically to a random sample, which includes several questions related to the health and physical aspects, and other questions related to the social aspects as well as the psychological aspects, before the spread of the pandemic and during the spread. The most important results that were obtained were: The physical and health motives were positively affected by the spread of Corona, as the importance of these motives exceeded the rest of the studied motives, especially during the spread of the pandemic, while the social motives were negatively affected during the spread of Corona, due to the fact that the Syrian society is of Communities with an active nature in social communication and exchange of visits. At the same time, direct social relations decreased during the spread of the pandemic, in order to avoid transmission methods, which the World Health Organization has long warned of due to the unique nature of the virus, while the psychological motives for practicing sports activities were not affected during this spread.